BATUAN ASAL DAN ALAS FORMASI PALEOGEN CEKUNGAN SERAYU - Bachri, S. (Jurnal Geologi dan Sumberdaya Mineral, 2012)
The occurrence of volcanic fragments within the most rock samples of the Worawari Formation, as indicated by SEM and petrographic analysis, suggest that the mainsource rock or provenance of the Worawari Formation is a volcanic rock. The volcanic rock, supposed to be Paleogene in age, was deposited in a short time on land before reworked transported and deposited in the sea, or partly formed as pyroclastic fall which was directly deposited in the sea as indicated by the occurrence of sedimentary structures, mainly wavy and parallel lamination. Meanwhile, a part of the rock samples of the Worawari Formation contain slate fragments suggesting that parts of source rock are metamorphic rock and a quartz rich rock. The quartz rich rock is supposed to be granitic basement as indicated by gravity data. This basement rock is Late Cretaceous in age, as indicated by fission-track dating using By zircon content in the Worawari Formation. The age suggests that the basement rock is apart of the Southeast Asian Plate or Sunda Platform.Key words : provenance, basement rock, Serayu Basin, Paleogen formation